2020
DOI: 10.1088/1361-6463/ab9c69
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen influence on electrical properties of Pt-contacted α-Ga2O3/ϵ-Ga2O3 structures grown on patterned sapphire substrates

Abstract: Here we report on the influence of various gases on electrical properties of Pt-contacted α-Ga2O3 and α-Ga2O3/ϵ-Ga2O3 structures produced by halide vapor phase epitaxy on planar and patterned sapphire substrates. Pt-contacted α-Ga2O3 structures were highly resistive and exhibited no sensitivity to H2 and other gases. In contrast, α-Ga2O3/ϵ-Ga2O3 structures grown under the same conditions on patterned sapphire substrates exhibited clear and reversible response to H2. The response to H2 was thoroughly investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 50 publications
(70 reference statements)
0
8
0
2
Order By: Relevance
“…When modeled LEDs were compared to planar LEDs, non-radiative recombination caused by high vector density becomes forward at a lower vector density. The sapphire substrate model for growing thin Ga 2 O 3 films can lower the energy barrier in LEDs, allowing more current to pass [83]. Zhou et al revealed that Ga 2 O 3 [84] based AlGaN UV LEDs with a specific resistance at contact about 2.36 ×10 3 cm 2 may achieve up to 93 % transmission at 365 nm.…”
Section: VIImentioning
confidence: 99%
“…When modeled LEDs were compared to planar LEDs, non-radiative recombination caused by high vector density becomes forward at a lower vector density. The sapphire substrate model for growing thin Ga 2 O 3 films can lower the energy barrier in LEDs, allowing more current to pass [83]. Zhou et al revealed that Ga 2 O 3 [84] based AlGaN UV LEDs with a specific resistance at contact about 2.36 ×10 3 cm 2 may achieve up to 93 % transmission at 365 nm.…”
Section: VIImentioning
confidence: 99%
“…Such α-Ga 2 O 3 /ε(κ)-Ga 2 O 3 structures grown by HVPE on PSS can be used in gas sensors. [13] In this article, we systematically investigated peculiarities of nucleation and luminescent properties of the Ga 2 O 3 layers grown by HVPE at different oxygen-to-gallium (VI/III ratio) ratios fluxes in a single process on PSS, GaN-on-sapphire templates, and m-plane sapphire substrates. We found that the threefold variation of VI/III ratio does not noticeably affect the luminescent intensity and spectra for all types of the substrates but changes distinguishably the growth rate for every kind of the layer.…”
Section: Introductionmentioning
confidence: 99%
“…Фаза ε-Ga 2 O 3 интересна тем, что обладает спонтанной поляризацией [2]. Оба указанных политипа оксида галлия уже сейчас опробованы для ряда применений [1,11,[17][18][19][20] в области электронных приборов и сенсоров.…”
Section: Introductionunclassified
“…В своей предыдущей работе [20] мы показали возможность разработки селективных датчиков низких концентраций H 2 в диапазоне рабочих температур 25−200 • C на основе структур α-Ga 2 O 3 /ε-Ga 2 O 3 с платиновыми контактами. Ключевым фактором для проявления чувствительности структур к водороду (H 2 ) является использование каталитически активного металла -платины (Pt) -в качестве электрода.…”
Section: Introductionunclassified